ÓZ BETINShE JUMÍSLAR ARQALÍ QARAQALPAQ TILINIŃ DIALEKTOLOGIYALÍQ MATERIYALLARÍN OQÍTÍW - Kaypnazarova, M.K. (SCIENCE and SOCIETY, 2025)
This article discusses the dialectological materials of the Karakalpak language and their analysis and study in lessons. The effectiveness of studying materials from the northern dialect of the Karakalpak language through independent work will be demonstrated through examples. The number of independent works is very large, but it is especially emphasized that the chosen methods of language material analysis facilitate a deeper study of text materials recorded in field practice.